2006
DOI: 10.1016/j.virol.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Specific and distinct determinants mediate membrane binding and lipid raft incorporation of HIV-1SF2 Nef

Abstract: Membrane association is believed to be a prerequisite for the biological activity of the HIV-1 pathogenicity factor Nef. Attachment to cellular membranes as well as incorporation into detergent-insoluble microdomains (lipid rafts) require the N-terminal myristoylation of Nef. However, this modification is not sufficient for sustained membrane association and a specific raft-targeting signal for Nef has not yet been identified. Using live cell confocal microscopy and membrane fractionation analyses, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 71 publications
5
86
0
1
Order By: Relevance
“…The role of membrane rafts in the assembly and budding of enveloped viruses has been investigated for influenza virus [59,63,[150][151][152][153][154][155][156][157][158][159][160], HIV-1 [63,[161][162][163][164][165][166][167][168][169][170][171][172][173], HTLV-1 [174], measles virus (Paramyxoviridae) [63,175,176], Sendai virus [Paramyxoviridae] [177,178], Newcastle disease virus (NDV; Paramyxoviridae) [179,180], RSV [147,148,[181][182][183][184], HSV [185,186], murine cytomegalovirus (MCMV; Herpesviridae) [187], Ebola virus [70,188], Marburg virus [70], and vesicular stomatitis virus (VSV; Rhabdoviridae) …”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of membrane rafts in the assembly and budding of enveloped viruses has been investigated for influenza virus [59,63,[150][151][152][153][154][155][156][157][158][159][160], HIV-1 [63,[161][162][163][164][165][166][167][168][169][170][171][172][173], HTLV-1 [174], measles virus (Paramyxoviridae) [63,175,176], Sendai virus [Paramyxoviridae] [177,178], Newcastle disease virus (NDV; Paramyxoviridae) [179,180], RSV [147,148,[181][182][183][184], HSV [185,186], murine cytomegalovirus (MCMV; Herpesviridae) [187], Ebola virus [70,188], Marburg virus [70], and vesicular stomatitis virus (VSV; Rhabdoviridae) …”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
“…Nef also binds to both the plasma membrane and viral structural proteins and participates directly in formation of the budding scaffold, leading to incorporation of Nef into virions, concomitantly with viral structural proteins [162,163,166]. The N-terminus of Nef determines the differential membrane avidities and selective incorporation into a specific membrane raft for surface membranes or for subcellular membranes [170]. Moreover, Nef modulates the lipid composition of virions and host cell membrane rafts through activation of lipid kinases such as PI3K [171].…”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
“…Based on biochemical and microscopic evidence, a subpopulation of membrane-associated Nef is incorporated into lipid microdomains in cell lines but also primary resting T lymphocytes [105][106][107]. This raft association depends on Nef's myristoylation and is specifically mediated by a di-lysine motif at the Nef N-terminus [107,108]. The use of experimental enrichment of raft association (by virtue of an additional palmitoylation) or abrogation of its raft incorporation (by mutating the di-lysine motif) revealed that raft-association is dispensable for the receptor transport activities of Nef [108,109].…”
Section: Hiv Nef: Remixing Raft Compositionmentioning
confidence: 99%
“…This raft association depends on Nef's myristoylation and is specifically mediated by a di-lysine motif at the Nef N-terminus [107,108]. The use of experimental enrichment of raft association (by virtue of an additional palmitoylation) or abrogation of its raft incorporation (by mutating the di-lysine motif) revealed that raft-association is dispensable for the receptor transport activities of Nef [108,109]. In contrast, signal transduction properties of Nef appear to be governed by the raft-associated Nef subpopulation.…”
Section: Hiv Nef: Remixing Raft Compositionmentioning
confidence: 99%
See 1 more Smart Citation